Cetnost výskytu úrazové ruptury aorty u posádek automobilů pri celním stretu se statickou ci dynamickou protijedoucí prekázkou - Hazuková, R; Hottmar, P; Lonský, V; Safr, M; Kunes, P (Soudni lekarstvi, 2002)
There is a lesion of aortic thoracic complex in car-passengers during the frontal clash to a static or to a dynamic antipodal obstacle is described in this study. It is a retrospective analysis. Facts were noted especially from dissectional documents. All from 298 men died. The main cause of car-passengers death was a weighty traumatic lesion of cardiovascular system in 58.7%. The aortic rupture was noted in 98 (32.9%) people, the death was in 90.8% directly on the road and 9.2% at hospital. From the whole people who were accepted to a hospital were 9 (8.9%) with a traumatic aortic rupture. But nobody of them was transported to a special center and everyone died due to traumatic lesion of cardiovascular system. Statistical significant cofactors of aortic rupture were atherosclerosis of aortic wall and intensity of clash. Therefore we can expect an aortic rupture in every third dead frontal car crash participant on a dynamic or static obstacle. Nearly 10% from men with traumatic aortic rupture were transported to a hospital. No aortic rupture was diagnosed.
Keywords: Accidents, Traffic; ženské pohlaví; ruptura aorty; dospělí; lidé; Female; mužské pohlaví; Male; Aorta, Thoracic; Aortic Rupture; aorta thoracica; Adult; dopravní nehody; Humans